Pengembangan Kampung E-Sport Dan UMKM Sebagai Wadah Remaja Produktif - Mohamad Bastomi; Moh. Isra Benasmi (Edumedia Solution, 2022)
The Islamic University of Malang (UNISMA) through the Institute for Research and Community Service (LPPM) held a Covid-19 Thematic Undergraduate Service Lecture (KSM). Students become volunteers to respond to the COVID-19 outbreak, which is expected to help the government provide education about Covid-19 to the public to stay alert and implement a healthy lifestyle during the Covid-19 pandemic, as well as ideas for activities while at home. KSM is carried out in the method used, namely online and offline socialization and education about preventing the spread of the Covid-19 virus. The media used are social media such as WhatsApp and Instagram. The results of the activities or programs that have been implemented are that the community realizes the importance of maintaining mental and physical health during the Covid-19 pandemic, providing education about 3M during the Covid-19 pandemic. In addition, to make teenagers productive, an E-Sport village idea was developed that serves as a forum for teenagers to play games professionally.